1998
DOI: 10.1038/2843
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol preference and sensitivity are markedly reduced in mice lacking dopamine D2 receptors

Abstract: Although dopaminergic transmission has been strongly implicated in alcohol self-administration, the involvement of specific dopamine receptor subtypes has not been well established. We studied the ethanol preference and sensitivity of D2-receptor-deficient mice to directly evaluate whether dopamine D2 receptors contribute to alcohol (ethanol) consumption. We report a marked aversion to ethanol in these mice, relative to the high preference and consumption exhibited by wild-type littermates. Sensitivity to etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
158
5
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(183 citation statements)
references
References 44 publications
18
158
5
2
Order By: Relevance
“…We and others have observed that D 2 KO mice exhibit significantly less locomotor activity than WT controls (Figures 2b and e) (Baik et al, 1995;Kelly et al, 1998;Phillips et al, 1998). D 2 KO mice also had a tendency to exhibit more circumscribed movements (increased spatial d; Figure 3).…”
Section: Discussionmentioning
confidence: 66%
“…We and others have observed that D 2 KO mice exhibit significantly less locomotor activity than WT controls (Figures 2b and e) (Baik et al, 1995;Kelly et al, 1998;Phillips et al, 1998). D 2 KO mice also had a tendency to exhibit more circumscribed movements (increased spatial d; Figure 3).…”
Section: Discussionmentioning
confidence: 66%
“…Electrophysiological, pharmacological, and genetic experiments have established a clear role for DA in voluntary ethanol consumption (eg, Koob et al, 1994;El-Ghundi et al, 1998;Phillips et al, 1998). For example, SA of ethanol increases nucleus accumbens (Nac) DA release in rodents (Weiss et al, 1993(Weiss et al, , 1996Gonzales and Weiss, 1998;Nurmi et al, 1998;Olive et al, 2000;Melendez et al, 2002;Hungund et al, 2003), and DA D1 and D2 receptor agonists and antagonists modulate ethanol SA in some circumstances (Weiss et al, 1990;Hubbell et al, 1991;Dyr et al, 1993;Rassnick et al, 1993a;Ng and George, 1994;Silvestre et al, 1996;Cohen et al, 1998Cohen et al, , 1999Boyce and Risinger, 2002;D'Souza et al, 2003;Zocchi et al, 2003).…”
Section: Ne and Ethanol Samentioning
confidence: 99%
“…For example, SA of ethanol increases nucleus accumbens (Nac) DA release in rodents (Weiss et al, 1993(Weiss et al, , 1996Gonzales and Weiss, 1998;Nurmi et al, 1998;Olive et al, 2000;Melendez et al, 2002;Hungund et al, 2003), and DA D1 and D2 receptor agonists and antagonists modulate ethanol SA in some circumstances (Weiss et al, 1990;Hubbell et al, 1991;Dyr et al, 1993;Rassnick et al, 1993a;Ng and George, 1994;Silvestre et al, 1996;Cohen et al, 1998Cohen et al, , 1999Boyce and Risinger, 2002;D'Souza et al, 2003;Zocchi et al, 2003). In addition, genetic deletion of D1 or D2 DA receptors decreases ethanol SA (El-Ghundi et al, 1998;Phillips et al, 1998;Risinger et al, 2000). However, inconsistencies similar to those obtained in examining the DA mediation of opiate reinforcement have plagued the field.…”
Section: Ne and Ethanol Samentioning
confidence: 99%
See 1 more Smart Citation
“…Although gene deletion and pharmacological studies have implicated both D 1 and D 2 receptors in mediating dopaminergic responses to EtOH administration (El-Ghundi et al, 1998;Phillips et al, 1998;Eiler et al, 2003;Inoue et al, 2007), the D 1 subtype appears to be particularly important with respect to the rewarding properties of EtOH and motivation for its consumption. For instance, administration of the D 1 receptor antagonists SCH23390 or ecopipam decreases EtOH consumption in mice, whereas administration of the D 1 agonist SKF81297 with EtOH facilitates alcohol-related behaviors (El-Ghundi et al, 1998;D'Souza et al, 2003;Price and Middaugh, 2004).…”
Section: Introductionmentioning
confidence: 99%